An assessment of the importance of the Dombes region, France, for wintering wildfowl - Fournier, Jean-Yves; Fouque, Carol; Defos du Rau, Pierre (Wildfowl, 2009)
Trends in the numbers of wildfowl wintering in the Dombes, France, from 1981–2006 were assessed to determine the importance of the site for these species at a national and international level. Spatial distribution patterns in relation to the size, hunting status and geographical location of the ponds were also investigated to identify some of the factors affecting the birds’ use of the site. Most species showed a moderate but significant increase in numbers (<5% per year) over the study period. Tufted Duck Aythya fuligula decreased in numbers from the early 1980s onwards whereas Shoveler Anas clypeata and Coot Fulica atra numbers started to decline in the early 1990s. Trends for the Dombes were similar to the national trends for each species except for Shoveler and Coot, which may have been influenced by local conditions. Within the Dombes, an increase in areas without hunting was found to explain local increases in numbers for most wildfowl species, but did not explain the decline in Shoveler and Coot. A management plan for the whole of the Dombes therefore should include assessing how the fishponds can improve the food supply for the birds, as well as providing further non-hunting areas.